2010
DOI: 10.1016/j.electacta.2009.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion regimes at nanoelectrode ensembles in different ionic liquids

Abstract: a b s t r a c tThe electrochemical and diffusion behaviour of different redox probes in different ionic liquids is studied at gold nanoelectrode ensembles (NEEs) in comparison with millimetre sized gold (Au-macro) and glassy carbon (GC) disk electrodes. The redox probes are neutral ferrocene (Fc), the ferrocenylmethyltrimetylammonium cation (FA + ) and the ferrocenylmonocarboxylate anion (FcCOO The CVs of the redox probes at the NEEs are peak shaped at low scan rate (v), while they are sigmoidally shaped at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
(68 reference statements)
5
16
0
Order By: Relevance
“…Transition from these conditions as a function of nanoelement distance has, nevertheless, been demonstrated experimentally by use of specially-made membranes [61]. It has recently been shown that, for NEE, transition from the total overlap to the pure radial diffusion can be observed on increasing electrolyte viscosity [67]. The voltammetric patterns recorded at NEEs in high-viscosity ionic liquids are, indeed, peak-shaped CV at low scan rates but become sigmoidally shaped at high scan rate (Fig.…”
Section: Current Signals At Neesmentioning
confidence: 96%
“…Transition from these conditions as a function of nanoelement distance has, nevertheless, been demonstrated experimentally by use of specially-made membranes [61]. It has recently been shown that, for NEE, transition from the total overlap to the pure radial diffusion can be observed on increasing electrolyte viscosity [67]. The voltammetric patterns recorded at NEEs in high-viscosity ionic liquids are, indeed, peak-shaped CV at low scan rates but become sigmoidally shaped at high scan rate (Fig.…”
Section: Current Signals At Neesmentioning
confidence: 96%
“…Depending on the distance between the nanoelectrode elements [17], the scan rate [17] and the viscosity of the electrolyte [18,19], different diffusion regimes can be observed. They are [1,2,20,21]: (A) total overlap regime, when radial diffusion boundary layers overlap totally; (B) pure radial, when the nanoelectrodes behave independently; (C) linear active, when the nanoelectrodes behave as isolated planar electrodes; (D) mixed diffusion regimes, that are regimes intermediate between cases (A) and (B).…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour is conceivably due to the rather low diffusion coefficients of ferrocene (D Fc ) and ferrocenium ion (D Fc+ ) in this medium, which lead to mixed radialplanar diffusion conditions [9,[20][21][22][23]. In fact, in RTILs, diffusion coefficient values for both Fc and Fc + in the range of 5 Â 10 À7 -10 À8 cm 2 s À1 were in general reported [9,[20][21][22][23][24][25][26][27][28].…”
Section: Voltammetric Measurements In the Pure Rtilmentioning
confidence: 83%